Drivers of spatiotemporal disparities in the supply-demand budget of ecosystem services: A case study in the Beijing-Tianjin-Hebei urban agglomeration, China - Li, Zu Zheng; Hu, Baoan; Qin, Yangyi; Cheng, Xiaoqin (Frontiers in Environmental Science, 2022)
Assessing the spatiotemporal patterns of ecosystem services (ESs) supply and demand, as well as the drivers thereof during specific time periods, is critical for regional policy making and sustainable management. Taking the Beijing-Tianjin-Hebei (BTH) urban agglomeration of China as an example, we studied four ES supply-demand systems: carbon storage, water provision, food provision and soil conservation from 2000 to 2015. Through the geodetector model, canonical analysis and Multiscale Geographically Weighted Regression (MGWR) model, the drivers of the ES supply-demand budget were explored. The results showed that the areas supplying high amounts of ESs in the northern region usually did not overlap those areas consuming intensive ESs, which were mainly distributed in metropolitan areas. The anthropological factors, including per capita gross domestic product (Per.GDP) and population density (POP.Den), were the dominant influencing factors for the imbalance between the supply and demand of carbon storage, water provision and food provision, which were mainly distributed in the central and southern regions of the study area. Geomorphological factors (ELE and SLO) were the key driving factors of soil conservation, which was mainly distributed in the eastern regions. In all, our findings could provide comprehensive information for decision-making and ES management.